2021
DOI: 10.1155/2021/8425206
|View full text |Cite|
|
Sign up to set email alerts
|

An Application for Measuring and Analyzing the Level of Performance Accuracy for Health Services Quality Indicators by Using Six-Sigma: A Study Case of Government Hospitals in Khartoum State

Abstract: The study aimed at acknowledging the Six Sigma methodology and the existence of the essential components for the application, as well as reducing the time for completing the operations, reducing the error rate to the lowest possible level, and improving the quality of operations. For this objective, the analytical descriptive methodology was used on a sample consisted of 300 administrative and medical staff from Khartoum State Hospitals (Khartoum, Omdurman, Bahri). To this end, a questionnaire was used for col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similar to how Total Quality Management, a key component of industrial engineering, gave rise to the Six Sigma approach used by Motorola Inc. in the 1980s. A data-driven approach to issue solving is called Six Sigma (5,6). The emphasis is placed on customer satisfaction, while the focus is on process variations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to how Total Quality Management, a key component of industrial engineering, gave rise to the Six Sigma approach used by Motorola Inc. in the 1980s. A data-driven approach to issue solving is called Six Sigma (5,6). The emphasis is placed on customer satisfaction, while the focus is on process variations.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%